Determinants of banks profitability: An evidence from GCC countries - Shoaib Khan (Journal of Central Banking Theory and Practice, 2022)
The research objective of the study is to investigate the determinants of profitability of banks' operating in GCC (Gulf Cooperation Council) countries. The existing studies highlight the banks' internal attributes and external factors that significantly influence profitability. The unbalanced panel data of 59 banks from the Bank scope database operating in six countries of GCC is used. Profitability is measured as return on assets (ROA) and return on equity (ROE) that have been used as dependent variables. Pooled OLS, fixed and random effects estimations are employed to explore the effect of explanatory variables internal factors, i.e. bank size, capital adequacy, asset quality, deposits ratio, asset management, operating efficiency and financial risk, and external factors, namely macroeconomic variables, GDP growth rate and inflation rate on dependent variables. Bank size and GDP growth have a significant and positive association with ROA. While Bank size and asset management have significant and positive impact, capital adequacy, financial risk, operating efficiency, and asset quality have a negative and significant impact on ROE. Fixed effects results are used for interpretation based on the Hausman test.
Keywords: G21; D02; E50; 330; Banks; profitability; macroeconomic; GCC; return onassets; return on equity